The association of TNF-α −308G/A and −238G/A polymorphisms with type 2 diabetes mellitus: a meta-analysis. Issue 12 (20th December 2019) - Guo, Xiaoliang; Li, Chenxi; Wu, Jiawei; Mei, Qingbu; Liu, Chang; Sun, Wenjing; Xu, Lidan; Fu, Songbin
Abstract: Tumor necrosis factor-α (TNF-α) is involved in insulin resistance and has long been a candidate gene implicated in type 2 diabetes mellitus (T2DM), however the association between TNF-α polymorphisms -308G/A and -238G/A and T2DM remains controversial. The present study sought to verify associations between these polymorphisms and T2DM susceptibility using a meta-analysis approach. A total of 49 case–control studies were selected up to October 2018. Statistical analyses were performed by STATA 15.0 software. The odds ratios (ORs) and 95% confidence intervals were calculated to estimate associations. Meta-analyses revealed significant associations between TNF-α −308G/A and T2DM in the allele model ( P =0.000); the dominant model ( P =0.000); the recessive model ( P =0.001); the overdominant model ( P =0.008) and the codominant model ( P =0.000). Subgroup analyses also showed associations in the allele model ( P =0.006); the dominant model ( P =0.004) and the overdominant model ( P =0.005) in the Caucasian and in the allele model ( P =0.007); the dominant model ( P =0.014); the recessive model ( P =0.000) and the codominant model ( P =0.000) in the Asian. There were no associations between TNF-α −238G/A and T2DM in the overall and subgroup populations. Meta-regression, sensitivity analysis and publication bias analysis confirmed that results and data were statistically robust. Our meta-analysis suggests that TNF-α −308G/A is a risk factor for T2DM in Caucasian and Asian populations. It also indicates that TNF-α −238G/A may not be a risk factor for T2DM. More comprehensive studies will be required to confirm these associations.